Minimally Invasive Open Lumbar Discectomy in Nepalese Patients: A Prospective Observational Study - Ram Chandra Shrestha,; Raj Kumar KC,; Adarsha Mahaseth,; Sameer Aryal, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTIONMinimally Invasive Open Lumbar Discectomy (MIOLD) is a muscle-sparing technique for lumbar disc herniation that may accelerate recovery while reducing morbidity. This study assessed its effectiveness, recovery profile, and safety in a Nepalese cohort.MATERIAL AND METHODSIn this prospective observational study, 70 adults (18–75 years) with MRI-confirmed lumbar disc herniation underwent MIOLD. Pain (Visual Analog Scale—VAS) and disability (Oswestry Disability Index—ODI) were recorded pre-operatively and at 24 h, 48 h, 1 month, and 3 months post-operatively. Additional outcomes included time to ambulation, hospital stay, return to daily activities, analgesic use, and complications. Continuous data are presented as mean ± SD; categorical data as n (%).RESULTSMean age was 46.8 ± 17.3 years; 60% male. Baseline VAS and ODI were 7.7 ± 1.2 and 55.1 ± 4.7%, respectively. At 24 h, VAS decreased to 2.4 ± 1.2; by 3 months it was 0.8 ± 0.4. ODI improved to 22.1 ± 2.3% at 1 month and 12.6 ± 1.6% at 3 months. Patients ambulated at 11.0 ± 2.0 h, achieved independent mobility in 3.0 ± 1.0 days, and resumed activities in 13.4 ± 2.4 days. All received NSAIDs; 31.4% received gabapentinoids, and 4.3% required opioids. Two dural tears (2.9%) and seven superficial wound infections (10.0%) occurred; no persistent CSF leaks or new neurological deficits were observed.CONCLUSIONMIOLD offers rapid and substantial pain relief, functional recovery, and a low complication rate, with early mobilization and short hospitalization, making it a viable option in resource-limited settings.